PI3K Inhibition Augments the Therapeutic Efficacy of a 3a-aza-Cyclopenta[α]indene Derivative in Lung Cancer Cells()() - Sanjiv, Kumar (Neoplasia Press, 2014)
The synergistic targeting of DNA damage and DNA repair is a promising strategy for the development of new chemotherapeutic agents for human lung cancer. The DNA interstrand cross-linking agent BO-1509, a derivative of 3a-aza-cyclopenta[α]indene, was synthesized and combined with the phosphoinositide 3-kinase (PI3K) inhibitor LY294002 to treat human lung cancer cells. Our results showed that the BO-1509 and LY294002 combination synergistically killed lung cancer cells in culture and also suppressed the growth of lung cancer xenografts in mice, including those derived from gefitinib-resistant cells. We also found that LY294002 suppressed the induction of several DNA repair proteins by BO-1509 and inhibited the nuclear translocation of Rad51. On the basis of the results of the γH2AX foci formation assays, LY294002 apparently inhibited the repair of DNA damage that was induced by BO-1509. According to the complete blood profile, biochemical enzyme analysis, and histopathologic analysis of major organs, no apparent toxicity was observed in mice treated with BO-1509 alone or in combination with LY294002. Our results suggest that the combination of a DNA cross-linking agent with a PI3K inhibitor is a feasible strategy for the treatment of patients with lung cancer.